Teachers’ Difficulties in Implementing Kurikulum Merdeka at SMK Negeri 1 Makassar - Haifa, Farha Sahafa; Sunra, La; Aeni, Nur (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
The objective of this study was to identify teachers’ difficulties in implementing Kurikulum Merdeka. The research utilized a descriptive qualitative approach, specifically employing a case study method. The subject of this research was teachers at SMK Negeri 1 Makassar. The researcher used an observation checklist and interviews as instruments to collect data in this research. Based on the findings of the researcher, the results show several difficulties for teachers in designing and implementing teaching modules, namely (1) teachers difficulties in determining the dimensions of the teacher's Pancasila student profile, (2) teachers have difficulties connecting lessons and teaching modules in vocational schools, (3) teachers face difficulties with the lack of school facilities and infrastructure, (4) teachers have difficulties recognizing the character of each student, (5) teachers have difficulties implementing teaching modules based on time allocation,(6) teachers have difficulties determining remedial measures. The results also show the teacher's efforts to overcome these problems are (1) by download the kurikulum merdeka package book, (2) teachers learn to understand each element in Pancasila student profile, (3) teachers increase their understanding of teaching module components, (4) teachers learn independently regarding the preparation of independent curriculum teaching modules.Keywords– Difficulties, Teaching Module, Kurikulum Merdeka